Effect of trans-nasal humidified rapid insufflation ventilatory exchange on reflux and microaspiration in patients undergoing laparoscopic cholecystectomy during induction of general anesthesia: a randomized controlled trial - Ding, Yinyin; Huang, Tianfeng; Ge, Yali; Gao, Ju; Zhang, Yang (Frontiers in Medicine, 2023)
Background: Reflux aspiration is a rare but serious complication during induction of anesthesia. The primary aim of this study was to compare the incidence of reflux and micro aspiration in patients undergoing laparoscopic cholecystectomy during induction of general anesthesia with either facemask or trans-nasal humidified rapid insufflation ventilatory exchange. Methods: We conducted a single-centre, randomised, controlled trial. Thirty patients were allocated to either facemask or trans-nasal humidified rapid insufflation ventilatory exchange (THRIVE) groups. Pre-oxygenation for five minutes with facemask or THRIVE, positive pressure ventilation for two minutes or THRIVE for two minutes after anesthesia induction. Before endotracheal intubation, the secretion above and below the glottis was collected to measure the content of pepsin and blood gas analysis was performed. Main outcome measures: ELISA assay for supra-and subglottic human pepsin content was used to detect the presence of reflux and micro aspiration. The primary outcome was the incidence of reflux and micro aspiration. Secondary outcomes were apnoea time, PaO2 before tracheal intubation and the end expiratory carbon dioxide partial pressure. Results: Patients in the THRIVE group had a significantly longer apnoea time (379.55 ± 94.12 s) compared with patients in the facemask group (172.96 ± 58.87 s; p<0.001). There were no differences observed in PaO2 between the groups. A significant difference in gastric insufflation, reflux and micro aspiration were observed between the groups. Gastric insufflation was 6.9% in the THRIVE group vs.28.57% kPa in the facemask group (p=0.041). Reflux was 10.34% in the THRIVE group vs. 32.14% kPa in the facemask group (p=0.044). Micro aspiration was 0% in the THRIVE group vs. 17.86% kPa in the facemask group (p=0.023). Conclusions: The application of THRIVE during induction of general anesthesia reduced the incidence of reflux and micro aspiration while ensuring oxygenation and prolonged apnoea time in laparoscopic cholecystectomy patients. THRIVE may be an optimal way to administer oxygen during induction of general anesthesia in laparoscopic cholecystectomy patients. Trail registration ： Chinese Clinical Trail Registry, No: ChiCTR2100054086, https://www.chictr.org.cn/indexEN.html